DELAYED CRACKING FAILURE OF A FREEZER BARREL - Albatros, Thomas; Ardy, Husaini (Jurnal Rekayasa Mesin, 2023)
Freezers were used to produce ice cream, pumped by a screw pump into a barrel. The barrel’s outer surface was operated with NH3 gas at -40 oC and a 12–13 bar pressure. After being in service for 3 years, the unit experienced cracking. The barrel material was Nickel 200, with a base metal average grain size of 48μm. The weld metal has a larger average grain size of 800μm and contains many gas pockets inside and along the grain boundaries, which coalesce one after another, forming micro-cracks that result in intergranular cracking. The weld metal failed in a brittle manner; this embrittlement was attributed to hydrogen atoms ingressing into the weld metal during welding. Atomic hydrogen will diffuse, forming hydrogen gas. Since atomic diffusion takes place over a long period, the occurrence of cracks is well-known as delayed cracking.